ASSESSMENT OF METABOLIC SYNDROME: ROLE OF SERUM FERRITIN - Sharma, Preeti; Kumar, Pradeep; Sharma, Rachna; K, Kishore; G, Sharma (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: The aim of the study is to explore the association between serum ferritin level and metabolic syndrome and its components. Methods: Serum ferritin level and metabolic syndrome and its components were measured among 100 study subjects with respect to 25 healthy controls at Santosh Medical College and Hospital, Ghaziabad. Fasting and post-prandial blood sugar level was estimated by using glucose oxidaseperoxidase (POD) method. Total cholesterol, triglycerides, and high-density lipoprotein cholesterol were estimated by using cholesterol oxidase (CHOD)-POD method, glycerol-3-phosphate oxidase-phenol aminophenazone method, and Phosphotungustate/CHOD-POD method, respectively. Low-density lipoprotein cholesterol was estimated by using Friedewald's equation. Serum concentration of ferritin was estimated by using Micro ELISA test kit. Cases and controls were compared using Chi-square test and unpaired Student's t-test and p values were calculated. Results: Significant relationship was observed between serum ferritin level and components of metabolic syndrome. Body mass index, blood sugar level, and lipid profile were significantly (<0.05) different between the groups. Serum concentration of creatinine and urea was not significantly (>0.05) different between the groups. Serum ferritin level was elevated in case group with metabolic syndrome and this difference was extremely significant (<0.01) between the groups. Conclusion: Serum ferritin, key regulator of iron homeostasis, can be used as indicator of progressing risk of metabolic syndrome. Keywords: Dyslipidemia, Ferritin, Insulin resistance.